Contrasting Contemporary Advertising Media Strategies of Small Retail Firms: - Reginald Masocha (Journal of Economics and Behavioral Studies, 2018)
This paper is an investigation contrasting modern and traditional advertising media from the perspective of small retail firms in Limpopo province of South Africa. Prior studies established juxtaposition in terms of media choices which continuously challenges businesses at large, per se, small retail businesses. A cross-sectional survey, through a purposive sampling technique of a subsequent sample size of 236 owners and managers of small retail firms was utilised in this research. Descriptive statistics, correlation and exploratory factor analysis (EFA) were used in data analysis. Furthermore, structural equation modelling (SEM) was used in hypotheses testing. The findings of the study posit that traditional advertising media have no significant influence on communication effectiveness and the performance of small retail SMEs. Contrarily, modern advertising media was found to positively and significantly influence the performance of retail SMEs. The practical implications of this study primarily pertain to the demise of traditional advertising media in the contemporary environments which business people need to consider. Theoretically, the study posits a review of the theory that pertains to the use of traditional media juxtaposed to modern media in contemporary advertising.